The time structure of hadronic showers in highly granular calorimeters with tungsten and steel absorbers - Adloff, Catherine; Briggl, Konrad; Harion, Tobias; Schultz-Coulon, Hans-Christian; Shen, Wei; Stamen, Rainer (Journal of Instrumentation, 2014)
The intrinsic time structure of hadronic showers influences the timing capability and the required integration time of hadronic calorimeters in particle physics experiments, and depends on the active medium and on the absorber of the calorimeter. With the CALICE T3B experiment, a setup of 15 small plastic scintillator tiles read out with Silicon Photomultipliers, the time structure of showers is measured on a statistical basis with high spatial and temporal resolution in sampling calorimeters with tungsten and steel absorbers. The results are compared to GEANT4 (version 9.4 patch 03) simulations with different hadronic physics models. These comparisons demonstrate the importance of using high precision treatment of low-energy neutrons for tungsten absorbers, while an overall good agreement between data and simulations for all considered models is observed for steel.